Evaluation of growth after liver transplantation in a group of Turkish pediatric patients (Annals of Medical Research, 2021)
Aim: Growth failure is considered as an important predictor of negative outcomes after liver transplantation (LT). In our study we aimed to evaluate the growth of liver transplanted children both at the time of LT and on follow-up and to determine factors which are effective on growth. Materials and Methods: Seventy nine children were included in the study. Evaluation of growth just before the LT and post-LT 6th month,1st,2nd and 3rd years was done by using weight for age Z (WAZ) and height for age Z scores (HAZ). Results: Sixteen (20.3%) patients had HAZ score-2 SD (standard deviation) and 13 (16.5%) had WAZ score -2 SD. Stunting was detected in 17.8% and 23.5% of children with acute liver failure and chronic liver disease, underweight was present in 8.9% and26.5%of them, respectively (p=0.52 and p=0.037, respectively). Both HAZ and WAZ scores increased after LT, especially in the ﬁrst year. Not mean pre-LT WAZ but mean HAZ score was lower in children who died on follow-up (p=0.023).Conclusion: Malnutrition before LT is a common problem in children. As stunting is a factor that reduces the chance of survival after LT, prevention and correction is very important.
Keywords: Children; growth; liver transplantation; acute liver failure; chronic liver failure